1976
DOI: 10.1007/bf01220630
|View full text |Cite
|
Sign up to set email alerts
|

Axonal dwindling in early experimental diabetes. II. A study of isolated nerve fibres

Abstract: Summary. In a morphometric study of isolated fibres of the common peroneal nerve in short-term diabetic rats reduced fibre calibre was observed. No segmental demyelination or remyelination was found, but the nodes of Ranvier were slightly widened and paranodal bulbi were swollen relative to fibre calibre. It is suggested that axonal dwindling is the primary event in experimental diabetes. The reduction of the myelin sheath may be a consequence of the abnormal nerve cell offshoot. The results obtained suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 19 publications
3
28
0
Order By: Relevance
“…This is similar to our previous experiments, as is the chosen dose of streptozotocin (3,(13)(14)(15).…”
Section: Methodssupporting
confidence: 71%
See 3 more Smart Citations
“…This is similar to our previous experiments, as is the chosen dose of streptozotocin (3,(13)(14)(15).…”
Section: Methodssupporting
confidence: 71%
“…The axon calibre increases in controls during the experimental period, whereas it decreases in diabetic rats despite normal nerve internodal length and normal skeletal length (1,3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another report deals with a study of isolated nerve fibres from the rats used in the present study [8,9]. It appears from this study that decreased nerve fibre thickness in diabetic rats can also be shown with this technique.…”
Section: Discussionmentioning
confidence: 84%